2011
DOI: 10.1590/s0365-05962011000400010
|View full text |Cite
|
Sign up to set email alerts
|

Onicomicose por Scytalidium spp.: estudo clínico-epidemiológico em um hospital universitário do Rio de Janeiro, Brasil

Abstract: FUNDAMENTOS: O Scytalidium spp. é fungo filamentoso, saprobio do solo e plantas, considerado, atualmente, patógeno primário das unhas. A prevalência das infecções ungueais causadas por este fungo vem aumentando nas últimas décadas, embora ainda sejam poucos os trabalhos publicados sobre sua epidemiologia. OBJETIVO: Estudo clínico-epidemiológico dos pacientes portadores de onicomicose por Scytalidium spp. em um hospital universitário do Rio de Janeiro. MÉTODOS: Foram avaliados os dados clínico-epidemiológicos d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 12 publications
3
25
1
7
Order By: Relevance
“…The common clinical type of onychomycosis in this study was DLSO and the most common site of involvement was the toenail, which was in accordance with previous studies . Clinical manifestations between the DMP and NDM groups showed no statistical difference.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The common clinical type of onychomycosis in this study was DLSO and the most common site of involvement was the toenail, which was in accordance with previous studies . Clinical manifestations between the DMP and NDM groups showed no statistical difference.…”
Section: Discussionsupporting
confidence: 92%
“…Few studies reported that approximately 10% of patients infected with Scytalidium spp. had hand involvement and one study reported groin involvement . However, this study demonstrated that patients with NDM onychomycosis had no superficial fungal glabrous skin infection at other sites beyond the feet, which statistically differed from the DMP group.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Dermatophytes are the main causal agents of toenail mycoses; however, the prevalence of non‐dermatophyte moulds (NDM) has been increasing, particularly in tropical and subtropical regions, generally in developing countries where the costs of public and private health require careful consideration . Accurate diagnosis of the disease and identification of its aetiological agent are equally important; thereby, specific treatment may be initiated as soon as possible in cases of disease, and in cases of non‐infectious onychopathies, the ramifications of the expensive, long‐term use of medications with potential risks may be avoided.…”
Section: Introductionmentioning
confidence: 99%